PENGARUH TEAMS GAMES TOURNAMENT PADA PEMBELAJARAN PENDIDIKAN PANCASILA TERHADAP KECERDASAN EMSOIONAL SISWA KELAS IV SEKOLAH DASAR - Siti Nurkholifah; Otib Satibi Hidayat; Indah Wardatussa’idah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This experimental study aims to determine the effect of the Teams Games Tournament (TGT) model on the emotional intelligence of fourth-grade elementary school students in the subject of Pendidikan Pancasila. The research subjects consisted of two classes: Class IV A as the experimental class using the TGT model and Class IV B as the control class using the STAD model, with 30 students in each class. The emotional intelligence questionnaire was tested for validity and reliability through a trial involving. The post-test analysis showed a significant difference (Sig. 0.001 < 0.05) between the two groups, with the experimental class having a higher average score (93.73) compared to the control class (78.87). The implementation of the TGT model enhanced students’ empathy, self-control, and cooperation. The TGT model is recommended as an effective strategy for fostering emotional intelligence in Pancasila Education.